Hubungan Kualitas Produk dan Kualitas Layanan terhadap Kinerja Penjualan pada PT XYZ di Surabaya - Wibowo, Rudy; Sutejo, Bambang; Dewi, Pinky Pininta; Prakasa, Davis Febrinanto (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of product quality and service quality on sales performance at PT XYZ in Surabaya. A quantitative approach with a survey method was employed, involving 100 respondents who were active consumers. The research instrument was a structured questionnaire that had been tested for validity and reliability. Data were analyzed using multiple linear regression with SPSS. The results indicate that both product quality and service quality have a positive and significant effect on sales performance, either partially or simultaneously. Product quality shows a stronger influence compared to service quality, with a regression coefficient of 0.412. The adjusted R² value of 0.327 reveals that 32.7 percent of sales performance variation can be explained by the two variables, while the remaining 67.3 percent is influenced by other factors. These findings highlight the importance of integrating product quality and service quality to strengthen competitiveness in the beverage industry.